Formulation and quality evaluation of noodles with starchy flours containing high levels of resistant starch - Beverly Cheruto Too; Ngo Van Tai; Nguyen Minh Thuy (My University, 2022)
1Department of Food Technology, Hue University Vietnam 2Department of Food Technology, College of Agriculture, Can Tho University, Vietnam 3School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Thailand
Keywords: Hue; Food technology; Food composition and properties